The creation of a pediatric surgical checklist for adult providers - Diana Ioana Rapolti; Phyllis Kisa; Martin Situma; Elsa Nico; Thom Lobe; Thomas Sims; Doruk Ozgediz; Greg Klazura (BMC Health Services Research, 2024)
Abstract Purpose To address the need for a pediatric surgical checklist for adult providers. Background Pediatric surgery is unique due to the specific needs and many tasks that are employed in the care of adults require accommodations for children. There are some resources for adult surgeons to perform safe pediatric surgery and to assist such surgeons in pediatric emergencies, we created a straightforward checklist based on current literature. We propose a surgical checklist as the value of surgical checklists has been validated through research in a variety of applications. Methods Literature review on PubMed to gather information on current resources for pediatric surgery, all papers on surgical checklists describing their outcomes as of October 2023 were included to prevent a biased overview of the existing literature. Interviews with multiple pediatric surgeons were conducted for the creation of a checklist that is relevant to the field and has limited bias. Results Forty-two papers with 8,529,061 total participants were included. The positive impact of checklists was highlighted throughout the literature in terms of outcomes, financial cost and team relationship. Certain care checkpoints emerged as vital checklist items: antibiotic administration, anesthetic considerations, intraoperative hemodynamics and postoperative resuscitation. The result was the creation of a checklist that is not substitutive for existing WHO surgery checklists but additive for adult surgeons who must operate on children in emergencies. Conclusion The outcomes measured throughout the literature are varied and thus provide both a nuanced view of a variety of factors that must be taken into account and are limited in the amount of evidence for each outcome. We hope to implement the checklist developed to create a standard of care for pediatric surgery performed in low resource settings by adult surgeons and further evaluate its impact on emergency pediatric surgery outcomes. Funding Fulbright Fogarty Fellowship, GHES NIH FIC D43 TW010540.